COMPLEX PROXIMAL SEDIMENTATION FROM PLINIAN PLUMES: THE EXAMPLE OF TARAWERA 1886 - Sable J.E.; Houghton B.F.; Wilson C.J.N.; Carey R.J. (My University, 2006)
The 1886 eruption of Tarawera, New Zealand, was unusual for a Plinian eruption because it involved entirely basaltic magma, originated in a 17-km-long fissure, and produced extremely overthickened proximal deposits with a complex geometry. This study focuses on an 8-km-long segment cutting across Mount Tarawera where over 50 point-source vents were active during the 5.5-h eruption. A detailed characterization of the proximal deposits is developed and used to interpret the range of styles and intensities of the vents, including changes with time. We identify the four vents that contributed most heavily to the Plinian fall and evaluate the extent to which current volcanic plume models are compatible with the depositional patterns at Tarawera. Three proximal units are mapped that have phreatomagmatic, magmatic, and phreatomagmatic characteristics, respectively. Within the magmatic proximal unit, beds of like character are grouped into packages and delineated on scaled cross sections. Package dispersal is quantified by measuring the linear thickness half-distance (t1/2) in the planes of the fissure walls. Most packages have localized dispersals (low t1/2), indicating that Strombolian-style activity dominated most vents. The more widely dispersed packages (high t1/2) reflect contributions from additional transport regimes that were more vigorous but still contributed considerable material to the proximal region. We conclude that the geometry of the observed proximal deposits requires three modes of fall transport: (1) fallout from the upper portions of the Plinian plumes produced principally by vents in four craters; (2) sedimentation from the margins of the lower portions of the Plinian plumes including the jets and possibly the lower convective regions; and (3) ejection by weak Strombolian-style explosions from vents that did not contribute significant volumes of particles to the high plume. We suggest that the curvature of the velocity profile across the jet region of each plume (1–4 km height) was important, and that the lower velocity at the margins allowed proximal deposition of a large volume of material with a wide grain-size range.
Keywords: BASALTIC PLINIAN ERUPTION; TARAWERA 1886; PROXIMAL PLINIAN FALL DEPOSIT; ERUPTION DYNAMICS; JET SEDIMENTATION